STRATEGIC HUMAN RESOURCE MANAGEMENT PRACTICES - Zarnigor Jamshedovna Abdurakhmanova (Modern American Journals, 2025)
Strategic human resource management is moving quickly from a background function to a key engine of ability for organizations, especially in people-driven industries such as tourism. In Uzbekistan, with tourism now seen as a national priority, companies face mounting pressure to ensure their HR practices serve rather than limit long-term goals. This article shines a light on SHRM in the countries travel sector by analyzing survey data, highlighting the gap between foreign and domestic firms, and sketching a step-by-step plan to lift SHRM maturity. Evidence shows that foreign brands use formal, tech-laden HR systems whereas many local firms still operate through personal networks and make-do solutions. To close the gap, the study urges executives to champion digital tools, invest in leadership pipelines, and weave environmental and social goals into everyday HR work.
Keywords: Strategic human resource management (SHRM), tourism sector in Uzbekistan, HR practices in emerging markets, workforce development, human capital strategy, digital HR tools, succession planning, PESTEL analysis, green HRM, comparative HRM (local vs. international firms)